Polyacid material with cubic stacking structure as well as preparation method and application of polyacid material
By forming a polyacid material NiW-POM with a cubic stacking structure on a conductive substrate, the problems of expensive and poor stability of existing catalysts are solved, and low overpotential hydrogen production and good photo-assisted electrocatalysis under high current under industrial conditions are achieved. effect.
Patent Information
- Application Number
- CN202411556753.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-24
AI Technical Summary
Existing catalysts are expensive and have poor stability, making it difficult to meet the needs of low overpotential hydrogen production and good photo-assisted electrocatalysis under high currents under industrial conditions.
NiW-POM, a polyacid material with a cubic stacking structure, is used to form a three-dimensional nanocube stacking structure on a conductive substrate through hydrothermal reaction. It is used as an electrode material for photovoltaic electrocatalytic hydrogen evolution.
It achieves ultra-long-term catalytic stability and excellent catalytic activity, can produce hydrogen at low overpotential under high current under industrial conditions, and has good photo-assisted electrocatalytic performance.
Smart Images

Figure CN119352075A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode material preparation, and in particular to a polyacid material with a cubic stacking structure, a preparation method and an application thereof. Background Art
[0002] With the intensification of environmental pollution and the gradual depletion of traditional energy resources, the world is facing severe environmental and energy challenges. These problems not only threaten human health and survival, but also pose major risks to economic development and social stability. It is imperative to find and promote sustainable energy solutions and take effective environmental protection measures. Clean energy refers to energy types that have less impact on the environment during production and use, and can reduce greenhouse gas emissions and environmental pollution. It is a key way to achieve sustainable development and respond to climate change.
[0003] Hydrogen energy is regarded as an important clean energy due to its zero emission, renewable, high energy density, multifunctional application and technological progress. Compared with other clean energy sources, hydrogen energy has the advantages of high energy density, diversified hydrogen production methods, easy storage and transportation. The existing hydrogen production methods can be produced through fossil energy reforming, industrial by-product gas, water electrolysis and other methods. Among them, the disadvantages of fossil energy reforming method are high energy consumption, complex equipment, difficult operation and possible environmental pollution. The disadvantages of industrial by-product gas method are different hydrogen purity, limited production, limited geographical location and safety risks. Not only that, whether it is hydrogen production from fossil energy reforming or industrial by-product hydrogen production, they cannot get rid of the large amount of carbon dioxide emissions. Therefore, we finally chose renewable energy hydrogen production represented by water electrolysis, because its raw materials and the final reaction products are abundant and recyclable water on the earth, which can basically achieve zero pollution.
[0004] As a sustainable green fuel technology, hydrogen production by water electrolysis is of great significance for alleviating the energy crisis. Among the catalysts developed by the prior art, although precious metals and their derivatives have attracted attention due to their lower catalytic overpotential (such as Pt / C, RuO2 and IrO2), their high price and poor stability limit their further development and application. In addition, in some parts of my country, the phenomenon of abandoned light is common, which is a great waste of light resources. Therefore, the development of low-cost catalysts that can utilize abandoned light needs further development. Therefore, the present invention proposes a polyacid material with a cubic stacking structure and a preparation method and application thereof to solve the problems existing in the prior art. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to propose a polyacid material with a cubic stacking structure, a preparation method and application thereof, and a preparation method thereof, which solves the problem that the catalysts developed by the prior art are expensive and have poor stability.
[0006] In order to achieve the purpose of the present invention, the present invention is implemented by the following technical scheme: a polyacid material with a cubic stacking structure, comprising a conductive substrate and a polyacid material, characterized in that: the polyacid material is loaded on the conductive substrate in a three-dimensional nanocube stacking structure, and the molecular formula of the polyacid material is NiW-POM (Ni7(NiW 12 O 42 )(OH)4(H2O)8).
[0007] A further improvement is that the conductive substrate is one of foamed nickel, carbon cloth or carbon paper.
[0008] A method for preparing a polyacid material having a cubic stacking structure comprises the following steps: Step 1: first dissolve a water-soluble nickel source and a water-soluble tungstate source in deionized water to obtain a mixed solution; Step 2: The mixed solution obtained in step 1 is subjected to a hydrothermal reaction on the surface of a pre-prepared conductive substrate to obtain a polyacid material NiW-POM (Ni7(NiW 12 O 42 )(OH)4(H2O)8).
[0009] A further improvement is that in step 1, the water-soluble nickel source is selected from one or more of nickel nitrate hexahydrate, nickel chloride hexahydrate, nickel sulfate hexahydrate, and nickel acetate tetrahydrate, and the water-soluble tungstic acid source is selected from one or more of ammonium tungstate, sodium tungstate, and sodium tungstate dihydrate.
[0010] A further improvement is that in step 1, the molar ratio of metal ions in the water-soluble nickel source and the water-soluble tungstate source is 2-4:2, and the usage ratio of the water-soluble nickel source, the water-soluble tungstate source and deionized water is 0.2-0.4 mmol: 0.2 mmol: 60 mL.
[0011] A further improvement is that in step 2, the temperature of the hydrothermal reaction is set to 160-200°C, and the time is set to 10-14 h.
[0012] A further improvement is that in the step 2, the reaction product obtained after the mixed solution undergoes a hydrothermal reaction on the surface of the conductive substrate is sequentially washed, dried and cooled.
[0013] A further improvement is that the reaction product is washed with deionized water and anhydrous ethanol in sequence, and the reaction product is dried by vacuum drying after washing, with the drying temperature set at 40-70°C and the drying time set at 6-12 hours.
[0014] An application of a polyacid material with a cubic stacking structure, wherein the polyacid material is used as an electrode material for photovoltaic couple electrocatalytic hydrogen evolution under industrial conditions.
[0015] The beneficial effects of the present invention are as follows: the present invention prepares a polyacid material with a self-supporting three-dimensional nanocube stacking structure by loading a polyacid material with a three-dimensional nanocube stacking structure on a conductive substrate. The polyacid material not only has excellent catalytic activity exceeding that of ordinary polyacid materials, but also has ultra-long-term catalytic stability. It can simultaneously meet the needs of low overpotential hydrogen production under large current under industrial conditions and good light-assisted electrocatalysis, has excellent catalytic activity and stability, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0017] Figure 1 This is a scanning electron microscope scan of the polyacid material prepared in an embodiment of the present invention; Figure 2 is an X-ray diffraction pattern of the polyacid material prepared in an embodiment of the present invention; Figure 3 is a linear voltammetric curve of the hydrogen evolution reaction of the polyacid material prepared in the embodiment of the present invention and the Pt / C electrode in a 1 mol / L KOH solution; Figure 4 is a Tafel plot of the hydrogen evolution reaction of the polyacid material and the Pt / C electrode prepared in the embodiment of the present invention in a 1 mol / L KOH solution; Figure 5 This is a chronoamperometric stability test diagram of the hydrogen evolution reaction of the polyacid material and the Pt / C electrode prepared in the embodiment of the present invention in a 1 mol / L KOH solution; Figure 6 is a linear voltammetric curve of the oxygen evolution reaction of the polyacid material and the Pt / C electrode prepared in the embodiment of the present invention in a 1 mol / L KOH solution; Figure 7 is a Tafel plot of the oxygen evolution reaction of the polyacid material and the Pt / C electrode prepared in the embodiment of the present invention in a 1 mol / L KOH solution; Figure 8 It is a side view of the chronoamperometric stability of the oxygen evolution reaction of the polyacid material and the Pt / C electrode prepared in the embodiment of the present invention in a 1 mol / L KOH solution; Fig. 9 is a linear voltammetric curve of electrocatalytic water decomposition of the polyacid material and Pt / C||RuO2 prepared in an embodiment of the present invention in 1 mol / L KOH solution; Fig.10 This is a chronoamperometric stability test diagram of the polyacid material prepared in an embodiment of the present invention for electrocatalytic water decomposition in a 1 mol / L KOH solution; Fig.11 This is a photoresponse test diagram of the polyacid material prepared in an embodiment of the present invention for electrocatalytic water decomposition in a 1 mol / L KOH solution; Fig.12 This is a light-driven test diagram of the electrocatalytic water decomposition of the polyacid material prepared in an embodiment of the present invention in a 1 mol / L KOH solution.
[0018] Fig.13 It is a linear voltammetric curve of the polyacid material prepared in the embodiment of the present invention electrocatalytic water decomposition in a 6 mol / L KOH solution at 80°C. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The general structural formula of polyacid materials is [XxMmOy] q- , wherein X represents a heteroatom (central atom), M represents a ligand atom (polyatom), and its structure is type A (Keggin structure). The molecular formula of the polyacid material of the present invention is Ni7(NiW 12 O 42 )(OH)4(H2O)8, the present invention named it NiW-POM. Example
[0021] See also Figure 1 , Figure 2 The present embodiment provides a polyoxometalate material having a cubic stacking structure, including a conductive substrate and a polyoxometalate material. The polyoxometalate material is loaded on the conductive substrate in a three-dimensional nanocube stacking structure. The molecular formula of the polyoxometalate material is NiW-POM (Ni7(NiW 12 O 42 )(OH)4(H2O)8), the conductive substrate is one of foamed nickel, carbon cloth or carbon paper. In this embodiment, foamed nickel is selected as the conductive substrate.
[0022] The scanning electron microscope photo of the polyacid material with a cubic stacking structure in this example is as follows Figure 1 As shown, Figure 1 The middle left picture shows NiW-POM at 500 nm. Figure 1 The middle right picture shows NiW-POM at 10 μm. Figure 1 It can be seen that its morphology is composed of stacked nanocubes, with smooth and solid morphology and strong stability; The X-ray diffraction pattern of the polyacid material with a cubic stacking structure of this embodiment is as follows Figure 2 shown. Example
[0023] refer to Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 , Fig.11 , Fig.12 This embodiment provides a method for preparing a polyacid material having a cubic stacking structure, comprising the following steps: Step 1: First, 0.2-0.4 mmol (0.3 mmol in this embodiment) of a water-soluble nickel source and 0.2 mmol of a water-soluble tungstate source are placed in 60 mL of deionized water and magnetically stirred at room temperature. The stirring speed is set to 600 rpm and the stirring time is set to 30 min. After stirring, a light green mixed solution is obtained; The water-soluble nickel source is selected from one or more of nickel nitrate hexahydrate, nickel chloride hexahydrate, nickel sulfate hexahydrate, and nickel acetate tetrahydrate. In this embodiment, nickel nitrate hexahydrate is selected as the water-soluble nickel source. The water-soluble tungstic acid source is selected from one or more of ammonium tungstate, sodium tungstate, and sodium tungstate dihydrate. In this embodiment, ammonium tungstate is selected as the water-soluble tungstic acid source. The molar ratio of the metal ions in the water-soluble nickel source and the water-soluble tungstate source is 2 to 4:2. In this embodiment, the molar ratio of the metal ions in the water-soluble nickel source and the water-soluble tungstate source is 3:2. Step 2: Prepare the pretreated nickel foam as a conductive substrate in advance, and then fix the conductive substrate vertically at the bottom of the polytetrafluoroethylene-lined reactor, and then pour the mixed solution obtained in step 1 into the reactor, and allow the mixed solution to undergo a hydrothermal reaction on the surface of the conductive substrate in a constant temperature water heating box. The temperature of the hydrothermal reaction is 160-200 ° C, which is set to 180 ° C in this embodiment, and the hydrothermal reaction time is 10-14 h, which is set to 12 h in this embodiment. After the hydrothermal reaction, the obtained reaction product is washed with deionized water and anhydrous ethanol in sequence. After washing, the reaction product is dried by vacuum drying, and the drying temperature is 40-70 ° C, which is set to 55 ° C in this embodiment. The drying time is 6-12 h, which is set to 8 h in this embodiment. After drying, the reaction product is cooled to room temperature to obtain a polyacid material NiW-POM (Ni7(NiW 12 O 42 )(OH)4(H2O)8); The pretreatment steps of the nickel foam are as follows: first, the nickel foam is cut into nickel foam blocks, the size of the nickel foam blocks is (1-2)×(1-2)×(2-4) cm, and the nickel foam is cut into nickel foam blocks of 1×1×3 cm in this embodiment, and then the nickel foam blocks are ultrasonically cleaned with 1-4 mol / L (2 mol / L is selected in this embodiment) dilute hydrochloric acid solution, ethanol and deionized water in sequence, and the cleaning time is 15-30 min. In this embodiment, the cleaning time is set to 15 min. After cleaning, the nickel foam is dried in a vacuum oven at a drying temperature of 60-80°C. In this embodiment, the drying temperature is set to 60°C, and the drying time is 6-12 h. In this embodiment, the drying time is set to 12 h, to obtain the pretreated nickel foam. Example
[0024] This embodiment provides an application of a polyacid material having a cubic stacking structure, and the polyacid material is used as an electrode material in electrocatalytic water decomposition.
[0025] Test Case Figure 3 The linear voltammetric curve of the hydrogen evolution reaction between the product prepared in Example 2 and Pt / C in 1 mol / L KOH solution shows that at a current density of 1000 mA cm -2 When the overpotential of the embodiment is 299 mV and 308 mV respectively, after adding light assistance, it can be increased from 308 mV to 271 mV.
[0026] Figure 4 The Tafel curve of the hydrogen evolution reaction between the product prepared in Example 2 and Pt / C in 1 mol / L KOH solution shows that the Tafel slope of the example is 135.61 mV dec-1 After adding light assistance, it can be increased from 135.61 mV dec -1 Increased to 86.56 mV dec -1 , which is close to the Tafel slope of Pt / C (92.07 mV dec -1 ), confirming that NiW-POM has good electrocatalytic hydrogen evolution kinetics.
[0027] Figure 5 The chronoamperometric stability test diagram of the hydrogen evolution reaction of the product prepared in Example 2 in 1 mol / L KOH solution shows that at 1000 mA cm -2 At a current density of , the embodiment works stably for more than 300 h, and the current density retention rate is more than 75%, which proves that NiW-POM has good working stability in 1 mol / L KOH solution.
[0028] Figure 6 The linear voltammetric curve of the oxygen evolution reaction of the product prepared in Example 2 and RuO2 in 1 mol / L KOH solution shows that at a current density of 1000 mA cm -2 When the overpotential of the embodiment is 489 mV and 468 mV respectively, after adding light assistance, it can be increased from 468 mV to 440 mV.
[0029] Figure 7 The Tafel curve of the hydrogen evolution reaction of the product prepared in Example 2 and RuO2 in 1 mol / L KOH solution shows that the Tafel slope of the example is 144.67 mV dec -1 After adding light assistance, it can be increased from 144.67 mV dec -1 Increased to 141.02 mV dec -1 , confirming that NiW-POM has good electrocatalytic hydrogen evolution kinetics.
[0030] Figure 8 The chronoamperometric stability test diagram of the oxygen evolution reaction of the product prepared in Example 2 in 1 mol / L KOH solution shows that at 1000 mA cm -2 At a current density of , the embodiment works stably for more than 300 h, and the current density retention rate reaches 89%, which proves that NiW-POM has good working stability in 1 mol / L KOH solution.
[0031] Fig. 9The linear voltammetric curve of the product prepared in Example 2 and Pt / C||RuO2 in 1 mol / L KOH solution for electrocatalytic water decomposition shows that the current density is 1000 mA / cm 2 When photoassisted, the voltage of NiW-POM is 2.02 V. After adding light assistance, it can be increased from 2.02 V to 1.84 V, which is lower than Pt / C||RuO2 (1.87 V).
[0032] Fig.10 The chronoamperometric stability test diagram of the product prepared in Example 2 for electrocatalytic water decomposition in 1 mol / L KOH solution shows that at 1000 mA cm -2 At a current density of 1 mol / L KOH solution, NiW-POM can work stably for at least 300 h, and the current density retention rate is over 84%, which confirms that NiW-POM has good working stability in 1 mol / L KOH solution.
[0033] Fig.11 This is the light response curve of the product prepared in Example 2 in 1 mol / L KOH solution, which proves that NiW-POM has good light response ability.
[0034] Fig.12 This is the light-driven curve of the product prepared in this example in 1 mol / L KOH solution. The driving voltage is only 1.57 V, which proves that NiW-POM has good light response ability.
[0035] Fig.13 The linear voltammetric curve of the product prepared in Example 2 for electrocatalytic water decomposition in 6 mol / L KOH solution at 80 °C, with a current density of 1000 mA / cm 2 When , the voltage of NiW-POM is 1.76 V, which confirms that NiW-POM has good industrial application prospects.
[0036] The stability test of this test example was not conducted under industrial conditions, and the remaining high current densities met industrial requirements, with 80 °C 6M KOH being the industrial condition.
[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A polyacid material having a cubic stacking structure, comprising a conductive substrate and a polyacid material, characterized in that: The polyacid material is in a three-dimensional nanocube stacking structure supported on a conductive substrate. The molecular formula of the polyacid material is NiW-POM(Ni7(NiW 12 O 42 )(OH)4(H2O)8).
2. The polyacid material having a cubic stacking structure according to claim 1, characterized in that: The conductive substrate is one of foamed nickel, carbon cloth or carbon paper.
3. A method for preparing a polyacid material having a cubic stacking structure as claimed in claim 1, characterized in that: The following steps are involved: Step 1: first dissolve a water-soluble nickel source and a water-soluble tungstate source in deionized water to obtain a mixed solution; Step 2: The mixed solution obtained in step 1 is subjected to a hydrothermal reaction on the surface of a pre-prepared conductive substrate to obtain a polyacid material NiW-POM (Ni7(NiW 12 O 42 )(OH)4(H2O)8).
4. The method for preparing a polyacid material having a cubic stacking structure according to claim 3, characterized in that: In the step 1, the water-soluble nickel source is selected from one or more of nickel nitrate hexahydrate, nickel chloride hexahydrate, nickel sulfate hexahydrate, and nickel acetate tetrahydrate, and the water-soluble tungstic acid source is selected from one or more of ammonium tungstate, sodium tungstate, and sodium tungstate dihydrate.
5. The method for preparing a polyacid material having a cubic stacking structure according to claim 3, characterized in that: In the step 1, the molar ratio of metal ions in the water-soluble nickel source and the water-soluble tungstate source is 2-4:2, and the usage ratio of the water-soluble nickel source, the water-soluble tungstate source and deionized water is 0.2-0.4 mmol: 0.2 mmol: 60 mL.
6. The method for preparing a polyacid material having a cubic stacking structure according to claim 3, characterized in that: In the step 2, the temperature of the hydrothermal reaction is set to 160-200° C., and the time is set to 10-14 h.
7. The method for preparing a polyacid material having a cubic stacking structure according to claim 3, characterized in that: In the step 2, the mixed solution undergoes a hydrothermal reaction on the surface of the conductive substrate, and the resulting reaction product is sequentially washed, dried, and cooled.
8. The method for preparing a polyacid material having a cubic stacking structure according to claim 7, characterized in that: The reaction product is washed with deionized water and anhydrous ethanol in sequence, and is dried in a vacuum drying manner after washing, with the drying temperature set at 40-70° C. and the drying time set at 6-12 h.
9. An application of a polyacid material having a cubic stacking structure, characterized in that: The polyacid material is used as an electrode material for photovoltaic couple electrocatalytic hydrogen evolution under industrial conditions.